Use of flow Cytometry as a quick way to select low cost carbon sources for biodiesel and carotenoid production by the red yeast Rhodosporidium toruloides NCYC 921 - Freitas, Claúdia (2013)
Some yeasts like Rhodosporidium toruloides are oleaginous and can be used for biodiesel production. In addition, some strains are able to produce valuable carotenoid pigments which are of great commercial interest, contributing significantly to reduce the biodiesel production costs. Carotenoid extraction and quantification are time consuming, generate high amounts of waste and require the use of considerable amounts of biomass. Flow Cytometry (FC) can monitor carotenoids accumulation in yeasts, at line, and with a high statistical resolution, during growth. Moreover, during the cultivation it is important to assess cell physiological states, since injured or dead cells decrease the bioprocess yield. If this information is obtained near real time, it is possible to change the process control strategy in order to achieve the maximum lipid and carotenoid productivities. To obtain a more sustainable biodiesel production, it is also important to use low cost substrates, such as industrial by-products. In the present work, different low cost substrates were used as carbon sources [glycerol as a biodiesel byproduct, sugarcane molasses and carob pulp (syrup) as a cheap by-product of the food industry in the European south countries] to produce lipids and carotenoids by the yeast R. toruloides NCYC 921, and a comparison was made. Flow cytometry was used to monitor carotenoid content and cell viability (enzymatic activity, membrane potential and membrane integrity) during all the yeast cultivations.